EFFECT OF TOASTING ON THE FAT CONTENT OF SOYBEANS (Glycine max L. Merrill) - Petrov, Petar; Cvetanovska, Lenka; Beliěovska, Daniela; Mateva, Matea (University Ss. Cyril and Methodius in Skopje, 2024)
The purpose of this research is to determine the influence of thermal processing of soybeans on changes in its lipid status. Two soybean varieties, Pella and Ilindenka, were keyed in the research, and the analyses to determine the lipid composition of soybeans were carried out in raw and thermally processed "toasted" soybeans. The thermal treatment was performed by exposing the material to a temperature of 125 oC for 15 minutes. The purpose of heat treatment is inactivation of anti-nutritional compounds in the grain such as trypsin inhibitors and urease which are the main problem when using raw soybeans in the diet of monogastric animals. Due to the sensitive relationship of fats to thermal treatment, a comparative study was made in order to determine the oxidative degree of fats in soy. Based on the results obtained from the quantitative analyses carried out to determine the fat content in soybeans, it was concluded that the thermal treatment of soybeans does not cause changes in the content of total fats in soybeans, and with regard to the lipid profile, a difference was found between the content of total unsaturated fatty acids.
Keywords: soybeans; toasting; fats; fatty acids